Unique factorization and the fundamental theorem of arithmetic. Issue 1 (2nd January 2017) - Sprows, David
ABSTRACT: The fundamental theorem of arithmetic is one of those topics in mathematics that somehow 'falls through the cracks' in a student's education . When asked to state this theorem, those few students who are willing to give it a try (most have no idea of its content) will say something like 'every natural number can be broken down into a product of primes'. The fact that this breakdown always results in the same primes is viewed as 'obvious'. The purpose of this paper is to illustrate with a number of examples that the 'Unique Factorization Property' is a rare property and the fact that the natural numbers possess this property is 'fundamental' to our understanding of this number system.